Adsorption and separation of carbon dioxide and methane on carbonaceous adsorbents. Issue 11 (12th November 2021) - Song, X.; Gong, J.; Zeng, Y.; Zhan, X.; Wang, L.
Abstract: Adsorption and separation of carbon dioxide and methane on different carbonaceous adsorbents were analyzed and compared. Coconut shell‐based activated carbon has the highest adsorption capacity for two gases. Sips model describes the adsorption isotherms best. The separation factor on coconut shell‐based activated carbon is the highest under various conditions, reaching about 3.8. The adsorption capacity of the two gases is closely related to the specific surface area and micropore volume of the adsorbent. The adsorbed amount of each component in the mixture is less than that of the pure component under the same condition, indicating that there is a competition in the adsorption process. The total adsorbed amount of the two gases decreases as the proportion of carbon dioxide decreases, implying that the adsorption process is dominated by carbon dioxide adsorption. Additionally, the separation factor decreases with increasing temperature. Understanding the adsorption behaviors of pure and binary carbon dioxide and methane is important in treating biomass gas using carbonaceous adsorbents. Abstract : Adsorption and separation of carbon dioxide and methane on 8 kinds of carbonaceous adsorbents were studied. Coconut shell‐based activated carbon has the highest adsorption capacity and separation factor under any situations. The adsorbed amount of each component in the mixture is less than that of pure component at the same condition. It implies there is a competition in the adsorption process.